Synthesis and Characterization of Nano-sized Al2O3 Particle Reinforced ZA-27 Metal Matrix Composites. (2015) - Shivakumar, N.; Vasu, V.; Narasaiah, N.; kumar, Subodh
Abstract: Metal matrix composite (MMC) focuses primarily on improving specific strength, high temperature and wear resistance applications. In this article, the present study is concentrate on the synthesis and characterization of ZA-27 metal matrix composite (MMC) reinforced with nano-sized aluminium oxide (Al2 O3 ) particle in different weight percentage of 1, 3 and 5%. A stir casting followed by squeeze casting technique is used for the fabrication of these composite materials. Wear volume loss of the composites is measured using Pin-on-Disc testing machine at different operating conditions and different weight percentage of Al2 O3 Nanoparticles. Further the microstructures of worn samples were characterized with the help of Scanning Electron Microscope (SEM). The results indicated that the wear volume loss of the composites is decreased with the increase in Al2 O3 nanoparticles reinforcement.